مساهمة في دراسة تنوع العوالق النباتية في مياه سد الحفة - جرجور سمير; شريبا فدوى (Latakia University Journal -Biological Sciences Series, 2013)
يوضح البحث توزع العوالق النباتية phytoplankton في أربعة مواقع مختلفة في صفاتها البيئية في بحيرة سد الحفة، ودراسة بعض العوامل البيئية لمياه السد وتأثيرها على العوالق النباتية ( درجة الحرارة ،BOD، DO، pH،NO2، NO3، NH4، PO4 ). جمعت العينات من مناطق مختلفة من البحيرة خلال الفترة الممتدة من حزيران2011 حتى أيار 2012 بمعدل مرة إلى مرتين شهرياً، حيث أمكن تحديد 84 نوعاً من العوالق النباتية وزِّعت على المجموعات الآتية: 38نوعاً من الطحالب الذهبية Chrysophyta منها ( 36 نوعاً من المشطورات Diatomophyceae ونوعين من الطحالب الذهبية Chrysophyceae) و20 نوعاً من الطحالب الخضراء Chlorophyta ، و19نوعاً من الطحالب الزرقاء Cyanophyta . ونوعان من الطحالب النارية Pyrrhophyta ، و5 أنواع من الأوغلينات Euglenophyta . وأظهرت النتائج أن هناك تغيرات واضحة في الخصائص الفيزيائية والكيميائية للمياه خلال فترة الدراسة في مياه سد الحفة . This research aims to study the distribution of Phytoplankton in four locations which have different environmental specifications, in addition to study some environmental factors of Alhaffeh Dam water that affect the distribution of the phytoplankton (Temperature ,BOD, DO, pH, NO3, NO2, NH4, PO4). Samples were collected from different locations of the Dam basin from June 2011 to May 2012 once or twice a month. (84) species of Phytoplankton were identified and were distributed as: (38) species of Chrysophyta, (36) species of Diatomophyceae, (2) species of Chrysophycea, (25) species of Chlorophyta, (20) species of Cyanophyta, (2) species of Pyrrhophyta, and (5) species of Euglenophyta. The results show apparent changes in physical and chemical properties of water during this study. This is the first study of the phytoplankton on the water of Alhaffeh Dam.